Portaria SR/PRR1 nº 5, de 24 de janeiro de 2023 - Miguel Eduardo Rodrigues Paiva Junior (DMPF-e, Brasília, DF, 25 jan. 2023. Caderno Administrativo, p. 7., 2023)
Altera fiscal técnico e administrativo do Contrato nº 09/2022.